Striking the Balance Between Real Happiness and Materialistic Happiness: India Vs Finland - Dr. Periasamy P; Dr. Dinesh. N; Dr. Kambam Vedantan, (Indian Journal of Management and Language (IJML), 2024)
This endeavor is a promising attempt to find out the real materialistic happiness of human beings in the world, especially when compared to the world’s materialistic happiest nation with densely populated nation India by considering the factors which are already considered for the happiest study, like GDP, human development index, social welfare, individual freedom to make choices in life, generosity, degree of corruption in the country and good life expectancy. To try and find out the real factors for happiness in the world. Material happiness is available outside of human beings, whereas the real happiness lies within every one of us, which is beyond our measurement.